Value of vascular growth factors after stenting coronary arteries in patients with IHD - Dana Taizhanova; Roza Bodaubay (National Scientific Medical Center, 2019)
One of the most important achievements of medical science is the development and implementation of endovascular methods for treating ischemic heart disease, the volume of which is progressively increasing in relation to other methods of myocardial revascularization. As a result of data from various researchers, the mechanism for the development of coronary artery restenosis in patients with coronary artery disease undergoing endovascular interventions can be an inflammatory reaction, smooth muscle hyperplasia, formation of a wall clot and its organization, as well as the effect of an angiotensin-converting enzyme that activates angiotensin-II, an inducer and inhibits the activity of bradykinin, which inhibits cell growth. Recent studies of molecular and cellular mechanisms of restenosis in models of vascular damage in animals, as well as histological studies of human coronary arteries, have shown that the basis for the development of restenosis is the activation of migration and proliferation of vascular cells under the influence of growth factors caused by damage, which is a manifestation of angiogenesis and leads to neointima hyperplasia and neoadvention, narrowing the lumen of arteries. However, today there is no single point of view regarding the role of vascular growth factors in the development of the restenotic process, the number of studies highlighting the dynamics of the concentration of vascular growth factors in response to balloon expansion or implantation of coronary stents, and their possible role in the neointima formation and the restenosis development.